Metagenomic Sequencing of Diamondback Moth Gut Microbiome Unveils Key Holobiont Adaptations for Herbivory - Xia, Xiaofeng; Gurr, Geoff M.; Vasseur, Liette; Zheng, Dandan; Zhong, Huanzi; Qin, Bingcai; Lin, Junhan; Wang, Yue; Song, FengQin; Li, Yong; Lin, Hailan; You, Minsheng (Frontiers in Microbiology, 2017)
Herbivore specialists adapt to feed on a specific group of host plants by evolving various mechanisms to respond to plant defences. Insects also possess complex gut microbiotas but their potential role in adaptation is poorly understood. Our previous study of the genome of diamondback moth, Plutella xylostella, revealed an intrinsic capacity to detoxify plant defence compounds, which is an important factor in its success as a pest. Here we expand on that work with a complete taxonomic and functional profile of the P. xylostella gut microbiota obtained by metagenomic sequencing. Gene enrichment in the metagenome, accompanied by functional identification, revealed an important role of specific gut bacteria in the breakdown of plant cell walls, detoxification of plant phenolics, and synthesis of amino acids. Microbes participating in these pathways mainly belonged to three highly abundant bacteria: Enterobacter cloacae, Enterobacter asburiae, and Carnobacterium maltaromaticum. Results show that while the gut microbial community may be complex, a small number of functionally active species can be disproportionally important. The presence of specific enzymes in the microbiota community, such as supporting amino acid synthesis, digestion and detoxification functions, demonstrates the beneficial interactions between P. xylostella and its gut microbiota. These interactions can be potential targets for manipulation to provide novel pest management approaches.